Creation of Educational Videos Focused on Fundamental Passing Techniques in Football at MAN 2 Palu - sianto, Moh. Ifkhal; iskandar, Hendra; Rahmah, Rahmah; Usbah, Muh.; Suhendra, Tesa Alex (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The aim of this study is to create multimedia resources utilizing video tutorials focused on fundamental football passing techniques through the ADDIE framework. Material and Method. This research involves a procedural development approach utilizing the ADDIE model, which encompasses analysis, design, development, implementation, and evaluation. Data analysis techniques employed include qualitative descriptive analysis and quantitative descriptive analysis. The multimedia developed focuses on variations of inside foot football passing, presented as a video tutorial. It includes content that explains the fundamental techniques of football passing and demonstrates how to execute basic techniques using the inside of the foot. Results. The findings from the feedback provided by experts in football materials indicate that the multimedia for football passing is rated positively, achieving a percentage value of 85%. The feedback from technology and information specialists is exceptionally positive, with a remarkable percentage of 98.75%. The feedback from PJOK teachers is highly positive, achieving a percentage of 96.25%. Conclusion. The findings indicate that the learning video on football passing variations is appropriate for implementation in physical education, health, and recreation courses. The aim is to ensure that this study can be effectively tested, allowing for the determination of its effectiveness through three conducted tests. This study suggests that additional exploration could lead to the creation of more interactive learning tools, including the incorporation of augmented reality or mobile applications powered by artificial intelligence to offer immediate feedback to learners. Furthermore, it is essential to evaluate the effectiveness of this learning video within a wider framework that encompasses diverse schools and varying educational levels.